Personality and school performance: Incremental validity of self- and peer-ratings over intelligence - Bratko, Denis (Array, 2006)
This paper examines the relationship of self and other-assessed personality with school grades in 255 (88 male) Croatian pupils. Conscientiousness was the strongest personality correlate of school grades for both self and peer-ratings. Grades were also negatively correlated with self-assessed Extraversion and Emotional Stability, and positively correlated with peer-ratings of Autonomy. When cognitive ability was partialled out correlations between personality and school grades showed little change, indicating that the effects of personality on academic performance were independent of intelligence. Hierarchical regressions indicated that personality accounted for unique variance in school grades: 18% by self- and 25% by peer-ratings. Self-ratings had only marginal incremental validity over peer-ratings in predicting school grades (3%), while incremental validity of peer- over self-ratings was larger (9%).